Period and Hero in the Work of “O`Tgan Kunlar” - Shakirova Khadichakhan Nematjon qizi (Zien Journals, 2022)
In this article, it is written about Abdulla Kadiri's novel "Otgan kunlar", its characters, description of the work. Opinions related to the work are presented.
Keywords: literature; life work; history of Uzbeks; grief of the nation